Characterization of Sn-3.5Ag-1.0Cu lead-free solder prepared via powder metallurgy method - Iziana, Yahya; Noor Asikin, Ab Ghani; Mohd Arif Anuar, Mohd Salleh; Hamidi, Abd Hamid; Zainal Arifin, Ahmad; Mayappan, Ramani (Scientific.Net, 2013)
Link to publisher's homepage at http://www.scientific.net/